The influence of competitive anxiety of Chinese elite swimmers - Zhou, Y.; Jin, Z.; Wen, Y. (Frontiers in Psychology, 2024)
Background: Competitive anxiety is a common stress response in competitive environments, influencing sports performance, particularly among elite swimmers.